(untitled) (Research, Society and Development, 2022)
Considering that the health of the professional, as well as their quality of life, has repercussions on how they perform their functions within the work activity. The present work aims to address the mental health of nursing professionals who worked and work on the front line in the fight against the coronavirus. This is a cross-sectional observational study, descriptive, with a quantitative approach. The research was conducted in two hospitals of the public network of the city of São Luís/MA, and, from the application of questionnaires of sociodemographic data and SRQ-20, through the Google Forms platform to the selected group, and for analysis used the SPSS software (version 21), in order to obtain the descriptive statistics (mean, standard deviation and frequencies), r Pearson correlation and mean difference tests. Among the results, it can be observed that the main cause of the anguish and psychological suffering of these professionals was due to the lack of psychological preparation, the function within the hospital, the excessive workload, and the value of the salary. We noticed the need to take measures that contribute to the improvement of the health condition of these professionals, who live in direct contact with patients diagnosed with COVID-19; the zeal and care with these professionals are essential for the cure of these symptoms, as well as for the promotion of better health conditions for the public in general.